Progress in real-time photoacoustic imaging using optical ultrasound detection - Nuster, R.; Paltauf, G. (ALT Proceedings, 2026)
Optical  phase  contrast  full  field  detection  in combination  with  a  CCD-camera  can be  used  to record  acoustic  fields.  This  allows  to  obtain  two-dimensional photoacoustic  projection  images  in real-time. The present work shows an extension of the  technique  towards  full  three-dimensional photoacoustic  tomography.  The reconstruction  of the initial three dimensional pressure distribution is a two step process. First of all, projection images of the initial pressure distribution are acquired. This is done  by  back  propagating  the  observed  wave pattern  in  frequency  space. In  the  second  step  the inverse Radon transform is applied to the obtained projection  dataset  to  reconstruct  the  initial  three dimensional pressure distribution. An experiment is performed  using  a  phantom  sample  which mimics the  properties  of  biological  samples  to  show  the overall applicability of this technique for real-time photoacoustic imaging.